DEVELOPING AN INTERACTIVE PROJECT-BASED LEARNING E-LKPD TO FACILITATE CREATIVE MATHEMATICAL THINKING SKILLS - Andi Saputra Mandopa; Adek Nilasari Harahap; Puspa Riani Nasution (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The urgency of this research is due to the limited learning resources that support the development of creative thinking in mathematics, which is an essential skill in the 21st century. This research aims to develop an interactive E-LKPD based on Project Based Learning (PjBL) that is valid, practical and effective in facilitating creative mathematical thinking skills in junior high school students.. The method used is research and development (R&D) by applying the 4-D model which includes the stages of defining, designing (design), development, and dissemination. The resulting product was tested for validity by a team of material and design experts with an average score of 3.28, and its practicality and effectiveness were assessed through student and teacher responses with an average total practical score of 3.5. Evaluation of improving mathematical creative thinking abilities using PjBL-based E-LKPD shows an average score of 80.86, which is included in the very high category with a completeness level reaching 89.65%. Thus, the PjBL-based E-LKPD is suitable for use because it meets the criteria of being valid, practical and effective. The implication of this research is the need for further development of the model used to produce products that are higher quality and more effective in supporting the creative mathematical learning process.Urgensi penelitian ini dikarenakan masih terbatasnya sumber belajar yang mendukung pengembangan berpikir kreatif dalam matematika, yang merupakan keterampilan esensial di abad 21. Penelitian ini bertujuan untuk mengembangkan E-LKPD interaktif berbasis Project Based Learning (PjBL) yang valid, praktis, dan efektif dalam memfasilitasi kemampuan berpikir kreatif matematis pada siswa SMP. Metode yang digunakan adalah research and development (R&D) dengan mengaplikasikan model 4-D yang meliputi tahapan pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate). Produk yang dihasilkan diuji melalui validitas oleh tim ahli materi dan desain dengan skor rata-rata 3,28, serta kepraktisan dan keefektivannya yang dinilai melalui respon peserta didik dan guru dengan rata-rata total nilai praktis 3,5. Evaluasi peningkatan kemampuan berpikir kreatif matematis menggunakan E-LKPD berbasis PjBL menunjukkan skor rata-rata 80,86, yang termasuk dalam kategori sangat tinggi dengan tingkat ketuntasan mencapai 89,65%. Dengan demikian, E-LKPD berbasis PjBL layak digunakan karena telah memenuhi kriteria valid, praktis, dan efektif. Implikasi dari penelitian ini adalah perlunya pengembangan lebih lanjut pada model yang digunakan untuk menghasilkan produk yang lebih berkualitas tinggi dan efektif dalam mendukung proses pembelajaran kreatif matematis.